Spirituality-Based Leadership Transformation in Building Inclusive Schools: Study of Efforts to Improve the Quality of Education in the Midst of Social Challenges - Febriyanti Ghayatul Qushwa; Hefniy (Managere: Indonesian Journal of Educational Management, 2024)
This research focuses on the analysis of the application of spiritual-based leadership in building an inclusive educational environment and improving the quality of educational institutions. This study uses a qualitative approach with a case study method conducted in a school in East Java. Data was collected through in-depth interviews with principals, teachers, and students, as well as direct observation of interactions in the school environment. Documentation is also used as supporting data to enrich the information obtained. Data analysis techniques include identifying patterns and themes, interpreting the meaning of the interviews, and triangulating data to ensure the validity of the findings. The results of the study show that spiritual-based leadership contributes significantly to creating an inclusive and harmonious learning environment. Principals who apply spiritual values in their leadership are able to build an atmosphere that values differences, encourages mutual respect among students, and strengthens a commitment to integrity and ethics among staff and students. These findings also show that the application of spiritual values in leadership improves school operational efficiency, student learning motivation, and teachers' commitment to the teaching process. The implications of this study suggest that spiritual-based leadership can be an effective leadership model to improve the quality of education and create an ethical, inclusive, and conducive school environment for learning. This research makes theoretical and practical contributions to the development of educational leadership models in Indonesia.